Using hologram-based modules to address learning loss in elementary students - Vebrianto, Rian; Yovita, Yovita; Yusriadi, Muhammad; Efendi, Silvina (Intelektual Pustaka Media Utama, 2025)
Learning loss can be characterized by several things such as a lack of student interest in learning where students are not focused and easily lazy in learning. This learning loss will get worse if the material presented in the lesson is abstract in nature and cannot be seen in real terms by students. With the use of a hologram projector, this study intends to evaluate the efficacy of interactive learning media in the form of hologram-based learning modules. In this case, quasi-experimental research methodology through nonequivalent control group design was employed in this study. The sampling technique is purposive sampling. The two sample classes used are class VI A (control) VI B (experimental). The results of the independent t-test on sig. (2-tailed) of 0.0010.05 indicate a significant difference between the results of the control class and the experimental class. The effectiveness of the N-Gain pretest and posttest of student learning outcomes in the control class were 0.25 in the low category and 0.57 in the experimental class in the medium category. Therefore, the study findings indicate that hologram-based module, aided by a holographic projector, was deemed to be useful for use in the learning process. The conclusion of this study is that it is expected that teachers and educators will be able to employ engaging and tangible learning materials and be supported by technology, with the usage of holograms being one of the choices.